Etude photophysique et photochimique des herbicides sulfonylurées en milieu aqueux - Aziz, Saâdia (Université Mohammed V - Agdal, Faculté des Sciences, Rabat, 2010)
The photophysical and photochemical studies of a Sulfonylurea herbicide (thifensulfuron-methyl (TFSM), metsulfuron-methyl (MTSF) and prosulfuron (PRSF), have been investigated in a buffered aqueous solution. In the first part, the influence of pH on the spectroscopic properties was studied. This allowed the determination of the ground and excited state acidity constants. In the second part, the photolysis kinetics was studied as function as oxygen concentrations, using an HPK 125W lamp and followed up by the identification of photoproducts formed under continuous photo-irradiation. The photolysis products were identified by high performance liquid chromatography HPLC-DAD, HPLC-MS and HPLC-MS-MS. In order to obtain a better understanding of the photodegradation mechanism, a laser flash photolysis study was performed. By comparing the quenching rate constant obtained from triplet state quenching by molecular oxygen and from the Stern Volmer relation, the role of the singlet state in the photodegradation process was demonstrated. The photoproducts originating from both singlet and triplet excited states have been identified and hypothetical photodegradation pathways of the herbicides in aqueous solution are proposed.
Keywords: Chimie physique; Sulfonylurée; Photophysique; Photochimie; Photodégradation; Photolyse laser